Two factors that bind to highly conserved sequences in mammalian type C retroviral enhancers. - Manley, N R (1993)
The transcriptional enhancers of the Moloney and Friend murine leukemia viruses (MLV) are important determinants of viral pathogenicity. We used electrophoretic mobility shift and methylation interference assays to study nuclear factors which bind to a region of these enhancers whose sequence is identical between Moloney and Friend viruses and particularly highly conserved among 35 mammalian type C retroviruses whose enhancer sequences have been aligned (E. Golemis, N. A. Speck, and N. Hopkins, J. Virol. 64:534-542, 1990). Previous studies identified sites for the leukemia virus factor b (LVb) and core proteins in this region (N. A. Speck and D. Baltimore, Mol. Cell. Biol. 7:1101-1110, 1987) as well as a site, overlapping those for LVb and core, for a third factor (N. R. Manley, M. A. O'Connell, P. A. Sharp, and N. Hopkins, J. Virol. 63:4210-4223, 1989). Surprisingly, the latter factor appeared to also bind two sites identified in the Friend MLV enhancer, Friend virus factor a and b1 (FVa and FVb1) sites, although the sequence basis for the ability of the protein to bind these diverse sites was not apparent. Here we describe the further characterization of this binding activity, termed MCREF-1 (for mammalian type C retrovirus enhancer factor 1), and the identification of a consensus sequence for its binding, GGN8GG. We also identify a factor, abundant in mouse T-cell lines and designated LVt, which binds to two sites in the Moloney MLV enhancer, overlapping the previously identified LVb and LVc binding sites. These sites contain the consensus binding site for the Ets family of proteins. We speculate on how distinct arrays of these factors may influence the disease-inducing phenotype.